La villa di Galileo in Arcetri / Galileo's villa at Arcetri - Godoli, Antonio (I libri de «Il Colle di Galileo», 2016)
Villa Il Gioiello, built in the measured, harmonious style of the mid-16th century on the hill of Arcetri just outside Florence, is where Galileo spent his last years, under house arrest. Recently restored, it was not simply Galileo's prison, it was also an observatory, a place of study and maybe even a place of leisure when he was tending the small vineyard that grew just over the courtyard wall.